Development of epigenetic biomarkers for the identification of sex and thermal stress in fish using DNA methylation analysis and machine learning procedures. (15th November 2022) - Valdivieso, Alejandro; Anastasiadi, Dafni; Ribas, Laia; Piferrer, Francesc
Abstract: The sex ratio is a key ecological demographic parameter crucial for population viability. However, the epigenetic mechanisms operating during gonadal development regulating gene expression and the sex ratio remain poorly understood. Moreover, there is interest in the development of epigenetic markers associated with a particular phenotype or as sentinels of environmental effects. Here, we profiled DNA methylation and gene expression of 10 key genes related to sex development and stress, including steroidogenic enzymes, and growth and transcription factors. We provide novel information on the sex‐related differences and on the influence of elevated temperature on these genes in zebrafish, a species with mixed genetic and environmental influences on sex ratios. We identified both positive (e.g., amh, cyp11c and hsd11b2 ) and negative (e.g., cyp11a1 and dmrt1 ) correlations in unexposed males, and negative correlation ( amh ) in exposed females between DNA methylation and gene expression levels. Further, we combined DNA methylation analysis with machine learning procedures and found a series of informative CpGs capable not only of correctly identifying sex (based on cyp19a1a DNA methylation levels) but also of identifying whether males and females had been exposed to abnormally elevated temperature when young (based on amh and foxl2a DNA methylation levels, respectively). This was achieved in the absence of conspicuous morphological alterations of the gonads. These DNA methylation‐based epigenetic biomarkers represent molecular resources that can correctly recapitulate past thermal history and pave the way for similar findings in other species to assess potential ecological effects of environmental disturbances in the context of climate change.